2022
DOI: 10.3329/jbcps.v40i1.57053
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Accumulation Product: An Effective Obesity Index to Predict Metabolic Syndrome

Abstract: Background: Obesity is a significant risk factor in the development of metabolic syndrome (MetS). Lipid Accumulation Product (LAP) is an obesity index and has been proposed to be a predictor of metabolic syndrome. The present study aims to see the effectiveness of Lipid Accumulation Product as an obesity index to predict metabolic syndrome in a Bangladeshi population. Methods: This cross-sectional study was conducted in Department of Biochemistry and Molecular Biology, Bangabandhu Sheikh Mujib Medical Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…It may be mentioned that similar studies were done in the same hospital setting to predict metabolic syndrome using 'lipid accumulation product' and 'triglycerides and glucose index', which showed that people having normal weights could be metabolically obese and are at risk of diabetes mellitus or cardiovascular diseases or other related complications. 19,20 Our present study reinforces that individuals should be assessed early and periodically and by using VAI, clinicians can detect metabolic syndrome in a simple way, counsel their patients to consider lifestyle interventions, and thereby prevent a significant amount of morbidity and mortality.…”
Section: Discussionsupporting
confidence: 71%
“…It may be mentioned that similar studies were done in the same hospital setting to predict metabolic syndrome using 'lipid accumulation product' and 'triglycerides and glucose index', which showed that people having normal weights could be metabolically obese and are at risk of diabetes mellitus or cardiovascular diseases or other related complications. 19,20 Our present study reinforces that individuals should be assessed early and periodically and by using VAI, clinicians can detect metabolic syndrome in a simple way, counsel their patients to consider lifestyle interventions, and thereby prevent a significant amount of morbidity and mortality.…”
Section: Discussionsupporting
confidence: 71%
“…11 LAP is a by-product of WC and TG that was calculated using the formula (WC [cm] − 58) × (TG [mM]). The rationale to use LAP is that it simultaneously predicts obesity 12 , insulin resistance 13 and MetS itself. 14 1).…”
Section: Selection Of Variables To Construct a New Mets Severity Scorementioning
confidence: 99%
“…Recently introduced by Amato et al [19] and Kahn et al [20], the VAI and LAP are strong and useful indicators for measuring visceral obesity and body fat distribution. Several studies have been performed among various populations, including Korean, Indian and Bangladeshi populations, demonstrating that the LAP and VAI are effective markers for different obesity phenotypes and strong predictors of MetS [21][22][23]. Like the VAI, the DAI was also developed as a surrogate marker of dysfunctional adiposity [24].…”
Section: Introductionmentioning
confidence: 99%